Innovation, risk management, and proactive behavior: An insight into the aspects of entrepreneurial marketing in SMEs - Hassan, Hend S. H.; Abdelkader, Ahmed A. M. (Edelweiss Applied Science and Technology, 2024)
Innovation, risk management, and proactive behaviour are the primary rudiments of entrepreneurial marketing that drive success and augment the competitiveness of business firms. Hence, exploring the interlinkage of these entrepreneurial marketing strategies in detail and looking forward to their underlying influence on the competitiveness of small and medium-sized enterprises (SMEs) is a useful approach to getting an overview of the current standing of small and emerging businesses in this regard. Therefore, the current study intends to contribute to this paradigm by sampling a total of 400 respondents from 47 SMEs in Kuwait. Data was collected via a questionnaire, and the responses were analyzed using SPSS v23. The outcomes depicted that all three dimensions of entrepreneurial marketing strategies have a positive and strong correlation with each other and a pronounced impact on driving competitiveness in SMEs. It has been noted that the aspiration towards bringing innovation, taking and managing risk for the anticipated good of the firm, and a proactive mindset are among the cardinal aspects that are imperative for the success and overall competitiveness of a firm to evolve and thrive in a diverse corporate sector and adopt change for the better of the organizations as well as the involved stakeholders.